Interpretation by the Fund. (Pamphlet Series, 1968)
This paper discusses the power of interpretation conferred upon the IMF by Articles of Agreement. The power of interpretation is an internal one in the sense that at no stage of the interpretative process is there any recourse to an agency external to the IMF itself. Moreover, no special organ of the IMF itself has been created for the purpose of exercising this power. It is exercised by the same organs of the IMF-the Executive Directors and the Board of Governors-that exercise most of the other powers of the institution.